(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2009)
Verbal correspondence can be defined as the relationship between an individual’s verbal and nonverbal behavior. Research into verbal correspondence has used correspondence training, a technique that establishes keeps, diminishes or extinguishes non-verbal behaviors through the control of verbal behavior, in three phases: baseline, reinforcement of verbal behavior and reinforcement of the correspondence between verbal and non-verbal behaviors. These training sessions use three different sequences: say-do, do-say and say-do-say. This article reviews the research in the area of verbal correspondence in these three different sequences. Current studies are highlighted that are concerned with describing the phenomenon of correspondence and which, therefore, did not use experimental methodology and, consequently, did not perform correspondence training, but rather observed the emergence of natural verbal correspondence.